Work oriented continuing training for semi-skilled and unskilled employees : an example from the metal and electrial industry - Bauer, Waldemar [Verfasser]; Koring, Claudia [Verfasser] (My University, 2009)
"Semi-skilled and unskilled employees working in "reduced skill" areas have an important role to play in some branches. Despite the growing skilly requirements in the workplace, however, this particular employment group is underrepresented in terms of participation in continuing training. The present paper portrays a work oriented continuing training concept for semi-skilled and unskilled employees which was developed within the scope of a three-year project involving companies from the metal and electrial industry and which has undergone successful piloting. The concept facilitates systemisation and promotion of self-directed learning in the workplace and is capable of autonomous and relatively rapid implemention by companies." (Autorenreferat, BIBB-Doku)
Keywords: P 2.2 An- und Ungelernte; S 1.5.2 Berufliche Weiterbildung; L 2.1 Lernformen; Nicht formal Qualifizierter; Einfacharbeit; Qualifizierung; Lernen am Arbeitsplatz; Selbstgesteuertes Lernen; Projekt